Los Angeles County Juvenile Justice Crime Prevention Act Fiscal Year 2012-2013 Report - Fain, Terry (RAND Corporation, 2014)
California's Juvenile Justice Crime Prevention Act provides funds for counties to offer evidence-based programs for high-need juvenile probationers and at-risk youth. This report, based on the annual report to the state legislature, outlines the program's success for six outcome measures (completion of probation, restitution, and community service; arrests; probation violations; and incarcerations) and county-required supplemental outcomes.